Preparation method and application of NiCoS-PBA / g-C3N4 composite material
By preparing NiCoS-PBA/g-C3N4 composite material, the problems of poor conductivity and structural instability of Prussian blue electrode material are solved, and its desalination ability as a CDI electrode material is significantly improved, and its application potential in seawater desalination is enhanced.
Patent Information
- Application Number
- CN202311601914.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-11-28
AI Technical Summary
The existing Prussian blue and its analogs, as CDI electrode materials, have problems such as poor conductivity, unfavorable structure for ion transport and unstable frame, resulting in poor desalting ability.
NiCoS-PBA/g-C3N4 composite material is prepared by surface modification, element doping and material composite to improve the conductivity, ion transport efficiency and frame stability of Prussian blue, thereby improving its desalination rate as a CDI electrode material.
The desalting ability of NiCoS-PBA/g-C3N4 composite as CDI electrode material has been improved, making it have higher application potential in seawater desalination.
Smart Images

Figure CN117682635B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitive deionization, and in particular to a preparation method and application of a NiCoS-PBA / g-C3N4 composite material. Background Art
[0002] Seawater or brackish water desalination is considered to be one of the strategies that can effectively alleviate the freshwater crisis. Subsequently, seawater desalination technology has developed rapidly, such as reverse osmosis membrane separation, electrodialysis, multi-stage flash evaporation, multi-effect distillation, capacitive deionization and other technologies. Among them, capacitive deionization (CDI) is an emerging seawater desalination technology, which has the advantages of low energy consumption, simple operation, and easy electrode regeneration. It has good application potential in the field of seawater desalination.
[0003] The mechanism of CDI desalination can be divided into two types: double-layer desalination and pseudocapacitive desalination. The mechanism of double-layer desalination is that when a voltage is applied between electrodes, ions in the solution move to the surface of the electrode with opposite charge under the action of the electric field, i.e., Na + Move to the negative electrode surface, Cl - Move to the positive electrode surface, and then adsorb on the electrode surface to form a double layer with opposite charges, thus achieving desalination. The mechanism of pseudocapacitive desalination is: when voltage is applied between the electrodes, ions in the solution move to the electrode surface and react with the electrode material to produce a Faraday reaction, thereby converting Na + or Cl - Embedded into the electrode material, thus achieving the purpose of desalination. Compared with double-layer desalination, pseudocapacitive desalination greatly improves the desalination amount and charge efficiency.
[0004] Electrode materials are the key factors affecting the desalination effect of CDI. Commonly used pseudocapacitive desalination materials include metal oxides, two-dimensional layered materials, Prussian blue (PBA) and its analogues. Among them, Prussian blue and its analogues have the characteristics of strong lattice and large space, stable crystal structure during the embedding and de-embedding of alkali metal ions, and zero lattice strain. However, they also have the disadvantages of poor conductivity, structure that is not conducive to ion transport and unstable framework, resulting in poor desalination ability, which needs to be further improved. Summary of the invention
[0005] Based on the above content, the present invention provides a preparation method and application of a NiCoS-PBA / g-C3N4 composite material. Prussian blue is regulated by surface modification, element doping, material composite, etc., so as to improve the conductivity, ion transmission efficiency and framework stability of Prussian blue, thereby improving its desalination rate when used as a CDI electrode material for desalination.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a method for preparing a NiCoS-PBA / g-C3N4 composite material, comprising the following steps:
[0008] The NiCo-PBA precursor was prepared by coprecipitation of nickel salt, cobalt salt, sodium citrate and potassium ferrocyanide;
[0009] The NiCo-PBA precursor is prepared by chemical etching and hydrothermal synthesis.
[0010] The NiCoS-PBA is mixed with melamine and then calcined to obtain a NiCoS-PBA / g-C3N4 composite material.
[0011] The second technical solution of the present invention is a NiCoS-PBA / g-C3N4 composite material prepared according to the above-mentioned preparation method.
[0012] The third technical solution of the present invention is the application of the above-mentioned NiCoS-PBA / g-C3N4 composite material in the field of capacitive deionization technology.
[0013] A fourth technical solution of the present invention is a CDI electrode material, the raw materials of which include the above-mentioned NiCoS-PBA / g-C3N4 composite material.
[0014] The present invention discloses the following technical effects:
[0015] The preparation process of the invention is simple and easy to be prepared on a large scale industrially.
[0016] The NiCoS-PBA / g-C3N4 composite material prepared by the method of the present invention has a high desalination capacity when used as a CDI electrode material for desalination. The method of the present invention is of great significance for the application of Prussian blue materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 This is the XRD spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1.
[0019] Figure 2 This is the SEM spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1.
[0020] Figure 3 This is the high-magnification TEM spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1.
[0021] Figure 4 This is the low-magnification TEM spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1.
[0022] Figure 5 This is the Raman spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1.
[0023] Figure 6 Cyclic voltammetry curves of the electrode prepared from the NiCoS-PBA / g-C3N4 composite material prepared in Example 1 at different scan rates. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The first aspect of the present invention provides a method for preparing a NiCoS-PBA / g-C3N4 composite material, comprising the following steps:
[0030] The NiCo-PBA precursor was prepared by coprecipitation of nickel salt, cobalt salt, sodium citrate and potassium ferrocyanide;
[0031] The NiCo-PBA precursor is prepared into a hollow structured NiCoS-PBA by chemical etching and hydrothermal synthesis;
[0032] The NiCoS-PBA is mixed with melamine and then calcined to obtain a NiCoS-PBA / g-C3N4 composite material.
[0033] NiCoS-PBA / g-C3N4 composite material is a hollow heterogeneous composite material of g-C3N4 coated NiCoS-PBA.
[0034] In a preferred embodiment of the present invention, the cobalt salt is CoCl2.
[0035] The cobalt salt was replaced with other transition metal Me commonly used in the field, such as vanadium and bismuth. The results showed that the desalination capacity of the hollow heterogeneous composite material of g-C3N4 coated NiMeS-PBA was not as good as that of the NiCoS-PBA / g-C3N4 composite material prepared with cobalt salt as raw material. XPS peak analysis of Co 2p of NiCoS-PBA / g-C3N4 composite material before and after desalination showed that the valence state of Co ions changed to a certain extent. + After the insertion process, Co 2+ With Co 3+ The molar ratio (based on peak area) of Na + When inserted into the NiCoS-PBA / g-C3N4 structure, most of the Co 3+ The species is reduced to Co 2+ The XPS peaks of V 2p of NiVP-PBA / g-C3N4 before and after desalination were analyzed. + After the insertion process, V 4+ With V 5+ The molar ratio (based on peak area) increased from 0.15 to 0.22. The peak area comparison results of XPS peaks showed that after replacing V with Co, the reducibility of the composite material was enhanced and the desalination capacity was greatly improved.
[0036] In a preferred embodiment of the present invention, the molar ratio of the nickel salt, the cobalt salt, the sodium citrate and the potassium ferrocyanide is 1.2:0.8:1.8:1.2.
[0037] In a preferred embodiment of the present invention, the nickel salt is NiCl2.
[0038] In a preferred embodiment of the present invention, the step of preparing the NiCo-PBA precursor by coprecipitation of nickel salt, cobalt salt, sodium citrate and potassium ferrocyanide is specifically as follows:
[0039] Nickel salt, cobalt salt and sodium citrate are dissolved in water and ultrasonically processed to obtain solution I; potassium ferrocyanide is dissolved in water to obtain solution II; the solution II is added dropwise to the solution I with stirring, matured, centrifuged and dried to obtain a NiCo-PBA precursor.
[0040] In a preferred embodiment of the present invention, the step of preparing NiCoS-PBA from the NiCo-PBA precursor by chemical etching and hydrothermal synthesis comprises:
[0041] Dispersing the NiCo-PBA precursor in an acid solution and performing a first hydrothermal reaction to obtain a hollow NiCo-PBA;
[0042] The hollow NiCo-PBA is dissolved in a sulfur source solution and subjected to a second hydrothermal reaction to obtain NiCoS-PBA.
[0043] In a preferred embodiment of the present invention, the mass ratio of the NiCoS-PBA to the melamine is 1:4.
[0044] In a preferred embodiment of the present invention, the calcination is specifically carried out in an inert atmosphere, heating to 550° C. at a heating rate of 5° C. / min and keeping the temperature for 4 hours.
[0045] In a preferred embodiment of the present invention, the melamine is pretreated with a nitric acid solution or a hydrochloric acid solution before being mixed with the NiCoS-PBA.
[0046] The second aspect of the present invention provides a NiCoS-PBA / g-C3N4 composite material prepared according to the above preparation method.
[0047] The third aspect of the present invention provides the application of the above-mentioned NiCoS-PBA / g-C3N4 composite material in the field of capacitive deionization technology.
[0048] A fourth aspect of the present invention provides a CDI electrode material, the raw materials of which include the above-mentioned NiCoS-PBA / g-C3N4 composite material.
[0049] In a preferred embodiment of the present invention, the preparation method of the CDI electrode material may include the following steps: mixing the NiCoS-PBA / g-C3N4 composite material, the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, grinding them evenly, adding an appropriate amount of N-methylpyrrolidone (NMP) solvent (the amount of N-methylpyrrolidone is such that the mixture of the NiCoS-PBA / g-C3N4 composite material, the conductive agent acetylene black and the binder polyvinylidene fluoride forms a uniform slurry), stirring them into a uniform slurry, and evenly spreading the slurry on graphite paper with a coater (250 μm), vacuum drying, and obtaining the CDI electrode material; cutting them to the required size when using them.
[0050] The "room temperature" described in the present invention, unless otherwise specified, refers to 20-30°C.
[0051] Unless otherwise specified, the raw materials used in the embodiments of the present invention can be obtained through commercial sources.
[0052] Example 1
[0053] (1) Preparation of NiCo-PBA precursor: 1.2mmol NiCl2, 0.8mmol CoCl2 and 1.8mmol C6H5Na3O7·2H2O were dissolved in 60mL deionized water and ultrasonicated for 30min (60℃) to make them completely dissolved to obtain solution I. 1.2mmol K3[Fe(CN)6] was dissolved in 40mL deionized water and ultrasonicated for 30min to obtain solution II. Solution II was added dropwise to solution I, magnetically stirred for 6h (60℃), and aged for 24h. Centrifuged at 8000rpm / min for 10min, then washed with anhydrous ethanol and dried (60℃) to obtain NiCo-PBA precursor.
[0054] (2) Preparation of hollow NiCo-PBA: 50 mg of NiCo-PBA precursor was dispersed in 30 ml of HCl solution (2 mol / L), ultrasonicated at room temperature for 30 min, and then transferred to a polytetrafluoroethylene-lined stainless steel autoclave (50 mL) and kept at 120 °C for 3 h. After cooling, centrifugation was performed at 8000 rpm / min for 10 min, washed with anhydrous ethanol and dried (60 °C) to obtain hollow NiCo-PBA; the NiCo-PBA showed a cubic morphology with an average size of about 328.46 nm.
[0055] (3) Preparation of NiCoS-PBA: 30 mg of hollow NiCo-PBA was dissolved in 30 mL of 2 mol / L Na2S solution, and after ultrasonic treatment for 1 h, it was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 120°C for 10 h. After natural cooling, the NiCoS-PBA powder was collected by centrifugation and washed three times, and dried at 60°C to obtain NiCoS-PBA powder.
[0056] (4) Preparation of NiCoS-PBA / g-C3N4: Dry NiCoS-PBA powder and melamine were mixed in a ratio of 1:4 (mass ratio) to obtain a mixture. Before use, melamine was pretreated with 7 mol / L HNO3 solution (melamine and nitric acid solution, volume ratio 1:1) and 6 mol / L HCl solution (melamine and hydrochloric acid solution, volume ratio 1:1) in sequence. The pretreatment method was to stir with a glass rod for 10 minutes respectively. The mixture was placed in a quartz boat and placed in a tube furnace. In an inert atmosphere (N2), the temperature was kept at 550°C for 4 hours at a heating rate of 5°C / min to obtain a powdered NiCoS-PBA / g-C3N4 composite material. The specific surface area of the NiCoS-PBA / g-C3N4 composite material is 477.41 m 2 / g.
[0057] The desalination ability of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1 as a CDI electrode material was verified:
[0058] The capacitive deionization experiment was carried out using a homemade CDI device; the device consists of a plexiglass base, graphite paper, electrode sheet, rubber gasket, chamber support plate and anion exchange membrane (AEM). The AEM divides the cavity formed by the plate and the support into two chambers, each of which can accommodate about 18mL of solution. The square electrode (3×3cm) is close to the base and fixed by a rubber gasket. The experimental operation system consists of a CDI device, a DC power supply, a conductivity meter and an external computer. Among them, the conductivity meter monitors the conductivity changes of the desalination process in real time, and the DC power supply provides stable external power for the entire desalination process in constant voltage mode.
[0059] The electrode sheet is prepared by the following steps: the NiCoS-PBA / g-C3N4 composite material prepared in Example 1, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1, and the mixture is evenly ground in an agate mortar and transferred to a weighing bottle, and an appropriate amount of N-methylpyrrolidone (NMP) solvent is added (the amount of N-methylpyrrolidone is such that the mixture of the NiCoS-PBA / g-C3N4 composite material, the conductive agent acetylene black, and the binder polyvinylidene fluoride can form a uniform slurry), and a magnetic stirrer is used to stir for 1 hour to form a uniform slurry, and the obtained slurry is evenly spread on the graphite paper with a film applicator (250μm), and dried at 80°C in a vacuum drying oven. When used, it is cut to the required size of 3×3cm, which is the electrode sheet.
[0060] Taking NaCl solution as the object, at an operating voltage of 1.2V, when the initial NaCl concentrations were 200, 400 and 600 mg / L, the desalination capacity of NiCoS-PBA / g-C3N4 composite electrode for NaCl was 83.64 mg / g, 141.86 mg / g and 155.29 mg / g, respectively. It can be obviously seen that the NiCoS-PBA / g-C3N4 composite electrode has good desalination ability, and the desalination ability increases with the increase of initial NaCl concentration.
[0061] Taking FeCl3 solution as the object, at an operating voltage of 1.2V, when the initial FeCl3 concentrations were 200, 400 and 600 mg / L, the desalination amounts of FeCl3 by NiCoS-PBA / g-C3N4 composite electrode were 25.51 mg / g, 37.52 mg / g and 85.49 mg / g, respectively. It can be seen that the NiCoS-PBA / g-C3N4 composite electrode has a good removal ability for FeCl3, and the desalination capacity increases with the increase of the initial FeCl3 concentration.
[0062] Taking AgCl solution as the object, when the initial AgCl concentration was 600 mg / L and the voltage was 0.8V, 1.0V and 1.2V, the desalination amount of AgCl by NiCoS-PBA / g-C3N4 composite electrode was 42.71 mg / g, 48.43 mg / g and 68.7 mg / g, respectively. It can be seen that NiCoS-PBA / g-C3N4 composite electrode has good removal ability for AgCl, and the desalination ability increases with the increase of voltage.
[0063] Figure 1 This is the XRD pattern of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1. Figure 1It can be seen that the general characteristic peaks of NiCoS-PBA / g-C3N4 composite materials correspond to NiCo2S4 (PDF#73-1704), Co9S8 (PDF#65-1765) and C3N4 (87-1526). Among them: the diffraction peaks at 2θ of 31.58°, 38.32° and 55.314° correspond to the (311), (400) and (440) crystal planes of NiCo2S4, the diffraction peaks at 29.18° and 50.90° belong to the (311) and (440) crystal planes of Co9S8, and the diffraction peaks at 26.50° and 44.06° correspond to the (002) and (200) crystal planes of C3N4, indicating that the NiCoS-PBA / g-C3N4 composite material was successfully prepared. At the same time, NiCoS-PBA / g-C3N4 still retains the characteristic peaks of the NiCo-PBA precursor at the (200), (220) and (400) crystal planes corresponding to 17.48°, 24.82° and 35.379°, confirming the cubic structure of the NiCoS-PBA / g-C3N4 core.
[0064] Figure 2 This is the SEM spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1. Figure 2 It can be seen that it is a porous nanosheet stacking structure, and the electrolyte can fully contact the electrode material, thereby promoting a series of reactions to obtain a higher specific surface area and specific capacitance. The g-C3N4 sheet is evenly coated on the surface of a single nanocube, inhibiting the agglomeration of NiCoS-PBA.
[0065] Figure 3 and Figure 4 TEM spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1. Figure 3 It can be seen that there are three distinct lattice fringes with marking intervals of 2.99nm, 2.15nm and 2.60nm, which correspond well to the Co9S8(311), NiCo2S4(331) and C3N4(102) crystal planes. Figure 4 The hollow core-shell structure of NiCoS-PBA / g-C3N4 and the g-C3N4 nanosheets wrapped around it can be clearly observed.
[0066] Figure 5 This is the Raman spectrum of the NiCoS-PBA / g-C3N4 composite material prepared in Example 1. Figure 5 It can be seen that NiCo-PBA is located at 2165cm -1 The strong peaks near this point belong to the C≡N bonds of the PB structure. It can also be observed that the NiCoS-PBA / g-C3N4 sample has a peak at 2313-3151 cm -1There is a broad and weak Raman peak at 536 and 743 cm, which may be due to the Raman shift effect caused by metal elements (Ni, Co). The strong electron attraction property makes it easy for metal ions to pull electrons from the C≡N bond, resulting in a larger force constant and finally a change in Raman shift. -1 The scattering peaks at 2 and 3 correspond to the F 2g and A 1g vibration mode. In addition, at 1391cm -1 and 1585cm -1 The I bands correspond to the D band and G band of carbon, respectively. D / I G The value is 3.65, indicating that its internal structure has more defects and good conductivity.
[0067] The cyclic voltammetry curves of the NiCoS-PBA / g-C3N4 composite material prepared in Test Example 1 as an electrode at different scan rates. The test method is as follows: The cyclic voltammetry test is carried out on an electrochemical workstation, using a three-electrode system, the electrolyte is 1 mol / L NaCl solution, and it is carried out at room temperature. The NiCoS-PBA / g-C3N4 composite material is used as the working electrode, and the platinum (Pt) electrode and the Ag / AgCl electrode are used as the counter electrode and the reference electrode, respectively. The cyclic voltammetry (CV) measurement potential range is -1.5 to 1.5 V, and the scan rates are 50, 100, 1000 and 2000 mV / s.
[0068] Figure 6 The cyclic voltammetry curves of the electrode prepared from the NiCoS-PBA / g-C3N4 composite material prepared in Example 1 at different scan rates. Figure 6 It can be seen that the CV curve of NiCoS-PBA / g-C3N4 corresponds to the redox reactions of nickel ions, cobalt ions and iron ions at about -0.89 / -0.59, 0.199 / -0.276 and 0.54 / 0.316, respectively, which is a typical pseudocapacitive behavior. As the scan rate increases, the shape of the CV curve is similar, indicating good rate performance and reversibility. In addition, it can be observed that with the increase of the scan rate, the reduction peak and the oxidation peak are slightly offset, which is mainly because the process of ions in the electrolyte diffusing to the inner electrode surface is relatively difficult. At higher scan rates, the redox reaction is delayed and the reaction is incomplete, resulting in polarization of the electrode.
[0069] Comparative Example 1
[0070] The only difference from Example 1 is that CoCl2 in step (1) is replaced by VCl3.
[0071] The same effect verification as in Example 1 was carried out, and the results showed that: with NaCl solution as the object, at an operating voltage of 1.2V, when the initial NaCl concentrations were 200, 400 and 600 mg / L, the desalination amount of NaCl by the composite material electrode prepared in Comparative Example 1 was 33.26 mg / g, 77.13 mg / g and 85.71 mg / g, respectively. Compared with Example 1, the desalination capacity was relatively poor.
[0072] The prior art PBAs prepared by coprecipitation inevitably cause hydration of the PBAs lattice, contain a large number of vacancies and coordinated water in the material structure, and the Prussian blue material is prone to collapse after high-temperature cubic structure. The present invention uses element doping and composite and surface modification methods to make Prussian blue still maintain a good cubic structure after high-temperature calcination, and prepares a NiCoS-PBA / g-C3N4 composite material with a hollow core-shell structure. The doping of nickel ions provides more sodium storage sites, plays a supporting role in the stable structure, and can improve the transmission capacity of sodium ions and electrons. The g-C3N4 carbon shell and nanopores are cross-linked with each other, effectively improving the ion transmission rate. In addition, the gaps between single hollow cubes can effectively alleviate the volume effect, thereby stabilizing the local conversion reaction. Thanks to the special structural design and multi-metal synergy, the material has good charge and discharge stability, maintains a high specific capacity, and makes the composite electrode material have a high conductivity.
[0073] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a NiCoS-PBA / g-C3N4 composite material, characterized in that: The following steps are involved: A NiCo-PBA precursor is prepared by coprecipitation of nickel salt, cobalt salt, sodium citrate and potassium ferrocyanide; NiCoS-PBA is prepared by chemical etching and hydrothermal synthesis of the NiCo-PBA precursor; NiCoS-PBA is mixed with melamine and then calcined to obtain a NiCoS-PBA / g-C3N4 composite material; The cobalt salt is CoCl2; the nickel salt is NiCl2; the molar ratio of the nickel salt, the cobalt salt, the sodium citrate and the potassium ferrocyanide is 1-1.2:0.6-0.8:0.9-1.8:0.6-1.2; The steps of preparing the NiCo-PBA precursor by coprecipitation of nickel salt, cobalt salt, sodium citrate and potassium ferrocyanide are specifically as follows: dissolving nickel salt, cobalt salt and sodium citrate in water and ultrasonicating to obtain solution I; dissolving potassium ferrocyanide in water to obtain solution II; adding solution II dropwise to solution I, stirring, aging, centrifuging and drying to obtain NiCo-PBA precursor; the stirring time is 6 hours and the temperature is 60° C.; the aging time is 24 hours; the centrifugation is performed at 8000 rpm for 10 minutes; the drying temperature is 60° C.; The step of preparing NiCoS-PBA by chemical etching and hydrothermal synthesis of the NiCo-PBA precursor comprises: dispersing the NiCo-PBA precursor in an acid solution, performing a first hydrothermal reaction, and obtaining a hollow NiCo-PBA; The hollow NiCo-PBA is dissolved in a sulfur source solution and subjected to a second hydrothermal reaction to obtain NiCoS-PBA.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the NiCoS-PBA to the melamine is 1:2-4.
3. The preparation method according to claim 1, characterized in that: The calcination is specifically carried out in an inert atmosphere, heating the temperature to 550° C. at a heating rate of 5° C. / min and keeping the temperature for 4 hours.
4. The preparation method according to claim 1, characterized in that: The melamine is pretreated with a nitric acid solution and a hydrochloric acid solution before being mixed with the NiCoS-PBA.
5. The NiCoS-PBA / g-C3N4 composite material prepared according to the preparation method according to any one of claims 1 to 4.
6. Application of the NiCoS-PBA / g-C3N4 composite material as claimed in claim 5 in the field of capacitive deionization technology.
7. A CDI electrode material, characterized in that: The raw materials include the NiCoS-PBA / g-C3N4 composite material as described in claim 5.
Citation Information
Patent Citations
Preparation method of transition metal oxide / sulfide nano composite material
CN106966443A
Preparation method and application of cobalt Prussian blue / carbon nitride sphere composite photocatalyst
CN116603562A
Prussian blue analogue carbon-based electrode and preparation method and application thereof
CN117105356A